Neurotourism Insights: Eye Tracking and Galvanic Analysis of Tourism Destination Brand Logos and AI Visuals - Calderón Fajardo, Víctor; Anaya-Sánchez, Rafael; Rejón-Guardia, Francisco; Molinillo-Jiménez, Sebastián (Universidade do Algarve, 2024)
This pioneering study explores the intersection between Neurotourism, defined as the integration of neurosciences in tourism, and the perception of tourism Brand Personality (BP) through the advanced use of psychophysiology techniques, specifically Eye-Tracking (ET) and Galvanic Skin Response (GSR). It analyses how tourism destination brand logos/combination marks and images generated by artificial intelligence (AI) influence consumer attention and emotional response. Focusing on the five dimensions of BP proposed by Aaker (1997) - sincerity, excitement, sophistication, competence, and ruggedness - this study highlights significant differences in how men and women process and react to brand values associated with specific cities. Employing a rigorous methodological approach and the application of non-parametric statistical analyses, the findings reveal distinct patterns of visual attention and emotional responses across genders, emphasising the importance of considering BP in the marketing and design of tourism destination brand logos/combination marks. This work not only advances theoretical understanding of tourist consumer behaviour but also offers relevant practical implications for tourism marketing and destination management.
Perspectivas del Neuroturismo: Análisis de Seguimiento Ocular y Respuesta Galvánica de Logos de Marcas de Destinos Turísticos y Visuales de IA
Este estudio pionero explora la intersección entre el Neuroturismo, definido como la integración de las neurociencias en el turismo, y la percepción de la Personalidad de Marca (PM) turística a través del uso avanzado de técnicas de psicofisiología, específicamente el seguimiento ocular y la respuesta galvánica de la piel. Analiza cómo los logotipos/marcas combinadas de destinos turísticos e imágenes generadas por inteligencia artificial influyen en la atención del consumidor y la respuesta emocional. Centrándose en las cinco dimensiones de BP propuestas por Aaker (1997) - sinceridad, excitación, sofisticación, competencia y robustez - este estudio destaca diferencias significativas en cómo hombres y mujeres procesan y reaccionan a los valores de marca asociados con ciudades específicas. Empleando un enfoque metodológico riguroso y la aplicación de análisis estadísticos no paramétricos, los hallazgos revelan patrones distintos de atención visual y respuestas emocionales entre géneros, enfatizando la importancia de considerar la PM en el marketing y diseño de logotipos/marcas combinadas de destinos turísticos. Este trabajo no solo avanza en la comprensión teórica del comportamiento del consumidor turístico, sino que también ofrece implicaciones prácticas relevantes para el marketing turístico y la gestión de destinos.
Keywords: Inteligencia artificial - Proceso de datos; Neurotourism; Eye tracking; Galvanic Skin Response; Brand Personality